1988
DOI: 10.1002/apmc.1988.051640110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the viscosity of components on the phase structure and impact strength of polypropylene/ethylene‐propylene elastomer blends

Abstract: dynamischen Gleichgewichts zwischen dem Zerfallen und der Koaleszenz der Polymerpartikelchen interpretiert. Bei Elastomerkonzentrationen, die hOher als 15% liegen, korrelieren die Unterschiede zwischen der Schlagzahigkeit einzelner Polymermischungen mit der Partikelgr6Be des Modifizierungselastomeren. Eine Dispersion, deren Struktur noch feiner ist als die der mit optimalen Schlagztihigkeitseigenschaften, kann nur bei Verwendung von hochviskosen Polypropylenmatrizes hergestellt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…It is known, though, that the size of dispersed particles depends, among others, on interfacial tension which can be related to the Flory-Huggins interaction parameter [60,62,64,76]. The relationship of these parameters is supported also by the results presented above and the data of Table 1.…”
Section: Miscibility-structure-property Correlationssupporting
confidence: 60%
“…It is known, though, that the size of dispersed particles depends, among others, on interfacial tension which can be related to the Flory-Huggins interaction parameter [60,62,64,76]. The relationship of these parameters is supported also by the results presented above and the data of Table 1.…”
Section: Miscibility-structure-property Correlationssupporting
confidence: 60%
“…Blend morphology can also be used as an indicator for the determination of blend compatibility. Generally, a smaller phase size of the dispersed phase indicates better blend compatibility of the system, resulting in improved mechanical properties of the blends 13–19. Speri and Patrick13 suggested that the relatively high impact resistance of polypropylene (PP)/ethylene–propylene rubber (EPR) blends could be achieved in the blends with small and narrow particle size and particle size distribution, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…0 and a steeper increase in R with v should appear for lower p if the stepwise breakup mechanism is decisive. This type of dependence was observed for polypropylene/ethylene-propylene elastomer blends mixed in the chamber of a Plasticorder (94,119). For the transient breakup mechanism, R should be smaller for larger p for all the volume fraction of the dispersed phase.…”
Section: Phase Structure Development In Moltenmentioning
confidence: 63%
“…If m is changed at a constant d , p and Ca are changed simultaneously. Mostly, an increase in m at constant d and mixing conditions leads to a decrease in the droplet size in the whole concentration range (94,119). The effect of elasticity of the components has not been fully understood so far.…”
Section: Phase Structure Development In Moltenmentioning
confidence: 99%